Effectiveness and Safety of Analgesics in Oral and Maxillofacial Surgery using Cox-2 Selective Inhibitors: A Review (International Journal of Food and Nutritional Sciences, 2022)
Background: In surgical outpatients, nonsteroidal anti-inflammatory medications (NSAIDs) are the most often given analgesics. The main drawbacks of NSAIDs are renal failure, hemostatic function impairment, and gastrointestinal (GI) side effects (perforation, ulceration, and bleeding) (with long-term therapy). The COX-2 selective inhibitors (CSIs or Coxibs), a novel family of NSAIDs, were created with the intention of lowering the GI side effects of conventional NSAIDs while keeping their potent anti-inflammatory and analgesic qualities. This narrative review of the literature examines the effectiveness of CSIs as analgesics, their clinical safety, and their cost-benefit analysis in the management of pain following oral surgery.